1, 2, 4-Triazol-1-ium-p-chloro-phenacylids in hydroxyl binary solvent mixtures. Computational and solvatochromic study. Issue 1 (21st November 2022) - Melniciuc Puica, Nicoleta; Dimitriu, Dan Gheorghe; Closca, Valentina; Dumitrascu, Leonas; Dorohoi, Dana-Ortansa
Abstract: Triazolium ylids and their derivatives are used as precursors for a great number of compounds in pharmaceutical and industrial fields. Triazolium ylids are amphiliophilic compounds with separated charges on positive nitrogen belonging to heterocycle and on negatively charged carbon, named carbanion and covalently bonded to the positive nitrogen. These substances are used in situ. Consequently, their interactions with the liquids, especially with water and primary alcohols are very important. The data regarding solute-solvent interactions in ternary solutions of two 4-aryl-1, 2, 4-trazol-1-ium-p-chloro-phenacylids were obtained by solvatochromism and by quantum chemical computations. New information about the ternary solution anisotropy and about the potential energy of molecular interactions of the type of ylid-water and ylid-ethanol are given in this study.